Cultural differences in moral judgment and behavior, across and within societies. (April 2016) - Graham, Jesse; Meindl, Peter; Beall, Erica; Johnson, Kate M; Zhang, Li
Highlights: Cultures vary substantially in both moral judgments and moral behaviors. Cultural variations in morality within societies can vary as much as cultural variations in morality between societies. Cultural factors contributing to this variation include religion, social ecology (weather, crop conditions, population density, pathogen prevalence, residential mobility), and regulatory social institutions such as kinship structures and economic markets. This variability raises questions for normative theories of morality, but also holds promise for future descriptive work on moral thought and behavior. Abstract : We review contemporary work on cultural factors affecting moral judgments and values, and those affecting moral behaviors. In both cases, we highlight examples of within-societal cultural differences in morality, to show that these can be as substantial and important as cross-societal differences. Whether between or within nations and societies, cultures vary substantially in their promotion and transmission of a multitude of moral judgments and behaviors. Cultural factors contributing to this variation include religion, social ecology (weather, crop conditions, population density, pathogen prevalence, residential mobility), and regulatory social institutions such as kinship structures and economic markets. This variability raises questions for normative theories of morality, but also holds promise for future descriptive work on moral thought and behavior.